Structure of linear expansions with conditions of the Favar type - Glavan , V. A. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The structure of the linear extensions, the exterior power of which satisfy the Favard condition on separability of the bounded motions from zero, is investigated.